Obesity as a Risk Factor for the Ineffectiveness of Antiangiogenic Treatment of Neovascular Age-related Macular Degeneration - V. G. Likhvantseva; A. S. Gevorgyan; S. G. Kapkova; S. I. Rychkova; T. E. Borisenko (Oftalʹmologiâ)
Purpose: evaluation of obesity as a risk factor for poor outcome (ineffectiveness) of antiangiogenic treatment of patients with neovascular AMD.Patients and methods. Body mass index (BMI) was studied in 84 patients (92 eyes) with neovascular AMD who were treated with intravitreal injections of Eilea in a fixed mode.Results. It was found that a poor treatment outcome in the subgroup with disease progression was associated with obesity of 1–2 degrees; the average BMI in this subgroup (with a deterioration in the morphostructural parameters of the retina) significantly exceeds the indicators of ideal respondents, for comparison: 31.5 ± 0.8 versus 28.6 ± 1.1 (p = 0.04); and the incidence of obese individuals is dominant: 72 %. At the same time, a moderate inverse reliable relationship of BMI with another risk factor — systolic blood pressure (SBP) was found. In this regard, we suggested that obesity indirectly affects the outcome of treatment, since it is “tied” to systolic blood pressure (p = 0.01). An argument in favor of this assumption is a higher correlation coefficient of SAD with the outcome of treatment. The authors hypothesized that obesity contributes to the development of hypertension by increasing the risk of poor outcome of nAMD treatment. The hypothesis explained the association of obesity with the progression of morphostructural changes in the retina in the group of non-responsents with nAMD.Conclusion. Studies have demonstrated a causal relationship between obesity and the outcome of antiangiogenic treatment of patients with nAMD. The data obtained allow us to attribute OBESITY to moderate risk factors for a poor outcome of antiangiogenic treatment of patients with nAMD. Taking into account the fact that OBESITY is a modifiable factor that can be eliminated with certain efforts, opportunities are revealed to reduce the risk of an unfavorable outcome of treatment of patients with nAMD.